Effects of pre- gelatinized starch inclusion in pellet on growth and physiological parameters of two commercial aquaculture species - Muniandy, Nagakanmani (2018)
A 9-week study was conducted to compare the use of dietary corn starch (CS) or tapioca starch (TS), with or without being pre-gelatinized (PG), on the growth, feeding efficiencies, plasma biochemistry, whole-body proximate composition, muscle cholesterol, muscle fatty acid composition, intestinal short chain fatty acids (SCFA), and liver glycogen and histopathology of red hybrid tilapia (Orecohromis sp.). Triplicate groups of 20 fish (initial mean weight = 0.739 ±0.01 g) were fed their respective diets to satiation. Various pellet characteristics were also measured that included bulk density (BD), expansion ratio (ER), pellet durability index (PDI), water solubility index (WSI), water absorption index (WAI), and water stability (WS) while the surface microstructure was examined. Results showed that tilapia fed the TS diet had significantly lower growth (p < 0.05) than all other treatments, but was significantly improved when pre-gelatinized. In the PG dietary treatments, intestinal SCFA significantly decreased while plasma glucose, cholesterol and triglycerides as well as liver glycogen were significantly higher compared to the native starch diets. Whole-body proximate composition and muscle cholesterol were unaffected by dietary treatments, although fish in the CS treatment had significantly higher amounts of long chain polyunsaturated fatty acids compared to the other treatments. The PG diets had significantly higher PDI, WS, WSI and BD compared to native starch diets. The surface morphology generally showed a smoother surface for the PG diets. While dietary TS was inferior compared to CS for tilapia, the PG-TS diet significantly improved their growth and feeding efficiencies and moreover the PG diets led better pellet characteristics that are likely to have important implications to the production of aquafeeds. Therefore, for the second experiment the tapioca starch was chosen and tested with African catfish. Tilapia and African catfish are the common commercial species that been farmed world wide. A 7-week study was conducted to compare the use of dietary tapioca starch and pre gelatinized tapioca starch with or without IMO on the growth, feeding efficiencies and muscle proximate composition of African catfish, Clarias Gariepinus. Triplicate groups of 15 fish (initial mean weight = 6.2 ± 0.3 g) were fed their respective diets to satiation. Various pellet characteristics were also measured that included bulk density (BD), pellet durability index, water solubility index (WSI), water absorption index (WAI), and water stability (WS). Results showed that there are no significance differences between treatments in growth of catfish (p > 0.05). The native starches with and without iso- maltose shows significantly lower water stability while the pre- gelatinized starch with and without iso- maltose showing high water stability. The water absorption index also shows significantly different between the native starches and pre- gelatinized starch. In overall, pre- gelatinized starches reduced the feed intake without compromising growth. As well, there were some negative effects to the nutritive value of the fish but it was mitigated by the addition of the prebiotic. Therefore, the pre- gelatinized tapioca starch can reduce the cost of production and as well help to maintain the water quality.